Oro-ruminal sampling device and technique for rapid collection of rumen content and improved recovery of solid fractions for microbiome analysis - Miccoli, Florencia Estefanía (2024)
Rumen fistulation is a widely used procedure that allows for collection of ruminal contents. However, fistulation is an invasive and costly procedure that generally limits the number of animals that can be recruited for experiments, thus encouraging the use of alternative techniques such as the intra-esophageal tube technique. One of the challenges of this technique is the limited ability to collect solid fractions from the rumen content pool which may impact the microbial community structure in the sample, particularly affecting the recovery and characterization of solid adherent-bacteria. We developed an intra-esophageal tube rumen sampling technique and device referred to as ‘Rumen Sampler MG’ with the aim of increasing the recovery of solid fractions from rumen content compared with other oro-ruminal sampling methods. The ‘Rumen Sampler MG’ device consists of a manual pump fitted with a barometer and an intra-esophageal flexible PVC tube with beveled terminal edge allowing for minimal clogging of the sampling tubing and a rapid flux of contents being sampled. Nine lactating Holstein-Friesian dairy cows (554.6 ± 25.2 kg BW; 8.3 ± 3.3 DIM) were recruited to evaluate the proposed method. During the procedure, animals were safely restrained in a chute and administered with a low dosage of a neuroleptic drug to reduce animal stress during sampling. An endoscopic camera was inserted into the reticulo-rumen through the esophagus to identify the sampling location and determine the length of the sampling tube necessary to reach the desired location. Following, the intra-esophageal sampling tube connected to a manual pump was inserted for collection of rumen contents. Samples collected did not present visual evidence of saliva contamination (e.g., high viscosity) and their pH ranged within expected values (6.33 - 7.04) for samples collected from the reticulo-rumen. Each sample contained 35–40% wet solids volume. Individual dry matter intake and milk production of cows continued to increase after sampling as expected for cows in the early postpartum period, suggesting that the sampling procedure did not affect cow performance. Results from microbiome analysis of rumen content samples suggest that the relative abundances of the main bacterial phyla are consistent with those from samples collected from dairy cows via rumen fistula in previous studies. The device and technique proposed allow for adequate samples of ruminal liquid and solid contents to be collected for microbiome analysis without disruption of animal performance.